1997
DOI: 10.1046/j.1365-2672.1997.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific peptides of casein pancreatic digestion enhance the production of tetanus toxin

Abstract: Casein pancreatic digest is the basic bacterial growth medium used for diphtheria, botulinumand tetanus toxin vaccine production. It is known that the variation in the peptide content of thecasein digest directly affects final toxin yields. In this study, the identification and sequences ofeight peptides, four to eight amino acids in length, of casein pancreatic digestion, which seem tobe involved in the enhancement of tetanus toxin production, are described. They all contain one ortwo residues of proline/mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…In addition to the studies already discussed in this paper, the complexity of the medium supplementation has been reported to interfere with specific metabolic pathways, such as control of glycogen metabolism in yeast 11 , secretion of enzymatic activities 9,17,25,[28][29][30]40,42 , primary 1 and secondary 8 metabolites. The effect induced by specific kinds of peptides on metabolic routes of nitrogen and carbon metabolism have also been considered.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In addition to the studies already discussed in this paper, the complexity of the medium supplementation has been reported to interfere with specific metabolic pathways, such as control of glycogen metabolism in yeast 11 , secretion of enzymatic activities 9,17,25,[28][29][30]40,42 , primary 1 and secondary 8 metabolites. The effect induced by specific kinds of peptides on metabolic routes of nitrogen and carbon metabolism have also been considered.…”
Section: Discussionmentioning
confidence: 85%
“…It is worth noting that there is an increasing interest in biologically active peptides released from proteins by enzymatic hydrolysis such as those obtained from milk proteins 20,27 . Recent studies have reported on the effect of specific peptides of casein pancreatic digestion on the production of tetanus toxin 28 and on the increased growth effect on lactic acid bacteria promoted by yeast extract filtrates 12 .…”
Section: Discussionmentioning
confidence: 99%
“…CO 2 seems to stimulate bont/B gene expression and subsequent neurotoxin production in C. botulinum type B (Lövenklev et al, 2004b). Moreover, short peptides from media containing pancreatic digest of casein are essential for toxin production by C. tetani (Porfirio et al, 1997). Growth temperature is a common signal involved in the control of alternative sigma factors and subsequent regulated gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting the increasing interest in biologically active peptides released from proteins by enzymatic hydrolysis such as those obtained from milk proteins 23,29 . In addition, recent studies have reported on the effect of specific peptides of casein pancreatic digestion on the production of tetanus toxin 30 and on the increased growth effect on lactic acid bacteria promoted by yeast extract filtrates 13 . The results presented in this work show that the structural complexity of the nitrogen source interferes with the fermentation performance of industrial baking and brewing ale and lager yeast strains.…”
Section: (-7'977-32mentioning
confidence: 99%